Molecular design of lower-oestrogen-activity phthalate acid esters with high fluorescence intensity using pharmacophore model. Issue 7 (28th May 2021) - Qiu, Youli; Jiang, Long; Zhang, Shujing; Li, Yu
ABSTRACT: A pharmacophore model for phthalate acid ester (PAE) oestrogen activity was constructed. Subsequently, hydrophobic groups at defined substitution sites were introduced to design new low oestrogen activity PAE derivatives. The PAE oestrogen activity pharmacophore model (Hypo 1) had the largest correlation coefficient (R 2 ) of 0.99, the smallest root mean square value of 0.31, and a configuration value of 16.87 (<17), indicating that the model has good predictive ability. Using the Hypo 1 model, 18 new PAE derivatives were designed, 16 of which had reduced oestrogen activity levels. Twelve PAE derivatives exhibited significantly enhanced fluorescence intensity (29- to 154-times), indicating that the derivatives can facilitate direct fluorescence detection. The functional properties of the derivatives were not significantly affected. The derivatives showed lower persistent organic pollutant (POP) characteristics, with maximum reductions of 29%, 69%, 1837%, and 79%, respectively. In addition, PAE and derivative docking with an oestrogen receptor revealed that hydrogen bonding and hydrophobic interaction were the main factors affecting oestrogen activity, and that energy, dipole moment, and Mulliken charge parameters controlled the fluorescence spectrum characteristics. The data provide a theoretical basis for designing plasticiser substitutes with high sensitivity to low oestrogen activity.